(untitled) (Research, Society and Development, 2022)
A balanced diet is essential in obesity control. Fruits stand out for the presence of various bioactive compounds, which represent promising tools in the prevention and treatment of various pathologies. In obesity, fruits phytochemicals present are related to different important mechanisms of action, such as antioxidant and anti-inflammatory activity. This narrative review aims to understand the main physiological alterations of obesity and the effects of bioactive compounds in fruits on them, identifying the best-known substances and their likely mechanisms of action on the main biomarkers. The research was carried out in the Google Scholar, Scielo, Pubmed and Science Direct databases, considering reviews published since 2015 and experimental studies since 2010. Inflammatory cytokines and adipokines are considered primary biomarkers of obesity, and are currently also considered the insulin resistance, lower glucose tolerance, oxidative stress, gut microbiota, nutrients and microRNAs. Three groups of fruits stood out for their effects: Citrus fruits, berries and tropical fruits, sources mainly of flavonoids, anthocyanins and carotenoids. Experimental results indicate that fruits and their compounds can help in the prevention and treatment of obesity through the regulation of inflammatory cytokines and adipokines involved in the mechanisms of this disease, as well as antioxidant properties and modulation of lipogenesis. More clinical studies are needed to understand the biochemical mechanisms involved, in order to favor not only the production of specific supplements but also the best clinical dietary prescription.